2022
DOI: 10.1088/2053-1591/ac37d4
|View full text |Cite
|
Sign up to set email alerts
|

Surface modification of recycled coir fibers with hybrid coating and its effect on the properties of ABS composites

Abstract: In this work, a hybrid coating (TSMA) was produced using tetraethyl orthosilicate (TEOS)/KH550/Styrene maleic anhydride copolymer (SMA) as raw materials. The coating was afterwards applied to modify recycled coir (r-coir) fibers via dip-coating. R-coir fibers reinforced ABS composites were then prepared and the reinforcing effect of fibers on the composite structure was investigated, as well. The r-coir fibers coated with TSMA were hydrolyzed in air for 3 days. The SiO2 particles produced by sol-gel reaction o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…[8][9][10][11][12] To date, additives extracted from different natural plants including acrylic, para rubber tree, bamboo, pineapple leaf, kenaf, palm, and, oil palm empty fruit bunch have been mixed with ABS in filler and particle forms with different weight ratios, and their effects on the tensile behavior of ABS have been deeply investigated. [13][14][15][16][17][18][19][20][21] The literature has clearly put forth that the tensile properties of ABS such as elastic modulus and yield strength are pronouncedly influenced by additives type, size, form, and weight ratios. [13][14][15][16][17][18][19][20][21] For 1 instance, the experimental study revealed that the addition of wood sawdust with a size of 100-300 μm improves the tensile elastic modulus of ABS but results in a decrease in its tensile strength.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[8][9][10][11][12] To date, additives extracted from different natural plants including acrylic, para rubber tree, bamboo, pineapple leaf, kenaf, palm, and, oil palm empty fruit bunch have been mixed with ABS in filler and particle forms with different weight ratios, and their effects on the tensile behavior of ABS have been deeply investigated. [13][14][15][16][17][18][19][20][21] The literature has clearly put forth that the tensile properties of ABS such as elastic modulus and yield strength are pronouncedly influenced by additives type, size, form, and weight ratios. [13][14][15][16][17][18][19][20][21] For 1 instance, the experimental study revealed that the addition of wood sawdust with a size of 100-300 μm improves the tensile elastic modulus of ABS but results in a decrease in its tensile strength.…”
Section: Introductionmentioning
confidence: 99%
“…[13][14][15][16][17][18][19][20][21] The literature has clearly put forth that the tensile properties of ABS such as elastic modulus and yield strength are pronouncedly influenced by additives type, size, form, and weight ratios. [13][14][15][16][17][18][19][20][21] For 1 instance, the experimental study revealed that the addition of wood sawdust with a size of 100-300 μm improves the tensile elastic modulus of ABS but results in a decrease in its tensile strength. 13 The effects of the weight ratio of wood sawdust on the tensile properties of ABS were also studied and reported that increasing the weight ratio of wood sawdust from 9.1 wt% to 33.3 wt% leads to an improvement in the elastic modulus, but a deterioration in the tensile yield strength.…”
Section: Introductionmentioning
confidence: 99%